ANALISIS HUKUM ATAS PENGGUNAAN DAN PEMBUATAN AKTA NOTARIS SECARA ELEKTRONIK - TISKA SUNDANI (PREMISE LAW JURNAL, 2017)
In their development, some countries have implemented electronic notarial deeds in their national legal system, especially in the need for the guarantee of the authenticity in electronic information. The provision which regulates authentic deeds is in UUJN (Notarial Act) and in the Civil Code which indicates that the use of notarial deeds and the drawing up authentic deeds are difficult to be implemented since there is no change in the understanding of authentic deeds stipulated in the notarial Act and in Law on ITE. The result of the research showed that the drawing up electronic deeds had become the beachhead of legal ground. For example, Article 15, paragraph 3 of UUJN and Article 17 of UUPT, include registration of electronic fiduciary deeds, registration of Notary electronically, amendment of articles of association of legal entity, etc. The obstacles of drawing up electronic deeds are influenced by some factors such as legal substance, legal structure, and legal culture. Keywords: Judicial Analysis, Technological Development, Notarial Deed